Lessons From the Commercial Failure of Project Loon for 6G Research Roadmap Design - Zhang, Liang; Zhang, Chuanting; Dang, Shuping; Shihada, Basem (Frontiers in Communications and Networks, 2022)
Currently, sixth-generation (6G) communication research roadmap is being frequently discussed and designed, in which, undoubtedly, aerial telecommunication infrastructures play crucial roles for boosting transmission capacity, enlarging coverage, and democratizing the benefits of information and communications technology (ICT) over the globe. However, the sudden news released in January 2021 that Alphabet is shutting down Project Loon, one of the most important projects enabling communications over aerial infrastructures, surprises the academia of communications science. There is no question that the failure of Project Loon will yield profound impacts on and even shift the current 6G research roadmap design. The latent mismatch between academia and industry in communication science should also raise adequate attention. Therefore, in this article, we analyze the commercial failure of Project Loon by public information from reliable sources and summarize a series of important lessons for the 6G research roadmap design.